Role of autogenic relaxation in management of diabetic cardiovascular autonomic neuropathy in type II diabetes mellitus patients - Verma, Manish K.; Biswas, D. A.; Tripathi, Shambhavi; Verma, N. S. (International Journal of Research in Medical Sciences, 2016)
Background: Cardiac autonomic neuropathy (CAN) is a very common complication of Type II diabetes mellitus patients. Early detection and treatment of CAN is necessary for reduction of mortality and morbidity in type II diabetes patients. Methods: The study included 120 diagnosed cases of type 2 diabetes mellitus with autonomic neuropathy both male & female, with more than 5 years duration of disease. Age group of the study subjects was between 30 – 70 years. All the 120 diabetic subjects were assessed for their heart rate variability. These 120 diabetic subjects were further divided in two groups by sealed envelope technique, with 60 subjects in each group. Subjects in Group I (Study group) were given relaxation therapy in the form of Rajyoga meditation, as guided by Rajyoga teachers. This group was asked to continue drug therapy for type 2 diabetes mellitus as prescribed by physician. On other hand, Group II (Control group) was given drug therapy as directed by physician but without relaxation therapy. At the end of 12 weeks HRV parameters, were re-evaluated and compared between the two groups. Results: Post intervention, Heart Rate Variability results showed that mean RR interval was significantly increased, whereas mean HR was significantly decreased in group I than in group II. All Time Domain parameters (i.e SDNN, RMSSD, NN50, pNN50 & Variance) were significantly increased in group I than in group II. The Frequency Domain parameter i.e LF/HF ratio was significantly decreased in group I than in group II. Thus the results showed that Raj Yoga meditation had a beneficial effect by improving the HRV parameters in diabetic patients with autonomic neuropathy. Conclusions: The study showed there is better improvement in all parameters of HRV in group I as compared to group II with the help of simple yet effective technique of Rajyoga meditation in type II diabetes mellitus patients with cardiac autonomic neuropathy.